2007
DOI: 10.1111/j.1751-228x.2007.00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalist Genes: Genetic Links Between Brain, Mind, and Education

Abstract: Genetics contributes importantly to learning abilities and disabilities—not just to reading, the target of most genetic research, but also to mathematics and other academic areas as well. One of the most important recent findings from quantitative genetic research such as twin studies is that the same set of genes is largely responsible for genetic influence across these domains. We call these “generalist genes” to highlight their pervasive influence. In other words, most genes found to be associated with a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 24 publications
3
41
0
2
Order By: Relevance
“…There is extensive support for genetic overlap across different domains of school achievement; high genetic correlations are invariably detected regardless of age, country, and subject (e.g. Davis et al 2009;Harlaar et al 2012;Hart et al 2010;Knopik and DeFries 1999;Kovas et al 2005;Oliver et al 2007;Plomin et al 2007). Evidence for the specificity of the unique environment is sparse.…”
Section: Generalist Genesmentioning
confidence: 96%
“…There is extensive support for genetic overlap across different domains of school achievement; high genetic correlations are invariably detected regardless of age, country, and subject (e.g. Davis et al 2009;Harlaar et al 2012;Hart et al 2010;Knopik and DeFries 1999;Kovas et al 2005;Oliver et al 2007;Plomin et al 2007). Evidence for the specificity of the unique environment is sparse.…”
Section: Generalist Genesmentioning
confidence: 96%
“…Genetic studies suggest that these disorders are highly heritable but also genetically complex (Paracchini et al 2007), with multiple genes influencing variance, and, Edited by Elena Grigorenko and Brett Miller. likely, some genes with generalist effects influencing a broad range of cognitive ability (Kovas and Plomin 2006)-corresponding to the genetic basis of what Spearman termed g. These studies also show a considerable specificity of gene effects, restricted to particular components of cognition in language and dyslexia (Bates et al 2007a). Importantly for theories of neurodevelopmental variation, the same genes appear to account for both normal variation and the majority of disorder (Bates et al 2007b, c, d;Plomin et al 2007).…”
Section: Introductionmentioning
confidence: 90%
“…Research highlights the crucial and dynamic role of environmental differences in performance outcomes (Shenk, 2010). Despite this, Plomin et al (2007) found that more than 90% of teachers and parents believe genetic influences to be more than or at least as important as environmental factors. Such beliefs have their origins in a long history of psychometrics in the UK (e.g.…”
Section: Introductionmentioning
confidence: 96%